On the Maximum Estrada Index of 3-Uniform Linear Hypertrees - Faxu Li; Liang Wei; Jinde Cao; Feng Hu; Haixing Zhao (The Scientific World Journal)
For a simple hypergraph H on n vertices, its Estrada index is defined as EE(H)=∑i=1n‍eλi, where λ1,λ2,…,λn are the eigenvalues of its adjacency matrix. In this paper, we determine the unique 3-uniform linear hypertree with the maximum Estrada index.